A novel human autoantigen, endothelial cell growth factor, is a target of T and B cell responses in patients with Lyme disease. Issue 1 (27th December 2012) - Drouin, Elise E.; Seward, Robert J.; Strle, Klemen; McHugh, Gail; Katchar, Kianoosh; Londoño, Diana; Yao, Chunxiang; Costello, Catherine E.; Steere, Allen C.
Abstract Objective Autoantigen presentation by HLA–DR molecules is thought to be a central component of many autoimmune diseases, but identifying disease‐relevant autoantigens has been a difficult challenge. In this study we aimed to identify autoantigens in patients with antibiotic‐refractory Lyme arthritis, in which infection‐induced autoimmunity is thought to play an important role. Methods Using tandem mass spectrometry, naturally presented HLA–DR self peptides from a patient's synovium were identified, synthesized, and reacted with his peripheral blood mononuclear cells (PBMCs). Immunoreactive peptides and their source proteins were then tested for T and B cell responses using large numbers of patient cells or sera. Results Of 120 HLA–DR–presented self peptides identified from one patient, one peptide derived from endothelial cell growth factor (ECGF) caused his PBMCs to proliferate. T and B cell responses to ECGF occurred systemically in ∼10–30% of patients with early or late manifestations of Lyme disease, primarily in those with refractory arthritis–associated HLA–DR alleles, such as DRB1*0101 and 0401. Compared with patients with antibiotic‐responsive arthritis, those with antibiotic‐refractory arthritis had significantly higher concentrations of ECGF in synovial fluid (P < 0.0001) and more often had ECGF antibody reactivity. Among non–antibiotic‐treated historical patients who developed arthritis, 26% had ECGF reactivity, which often developed before the onset of arthritis and was associated with significantly longer courses of arthritis. Conclusion T and B cell responses to ECGF occur in a subset of patients with Lyme disease, particularly in those with antibiotic‐refractory arthritis, providing the first direct evidence of autoimmune T and B cell responses in this illness.